Comparison of the antibacterial properties of Resin cements with and without the addition of nanoparticles: a systematic review - Ravinder Saini; Sunil Kumar Vaddamanu; Masroor Ahmed Kanji; Syed Altafuddin Quadri; Saeed Awod Bin Hassan; Sukumaran Anil; Deepti Shrivastava; Kumar Chandan Srivastava (BMC Oral Health)
Abstract Resin cement exhibits numerous therapeutic advantages over conventional luting materials. However, the effectiveness of the antibacterial properties of resin cement remains unclear. Nanotechnology provides a viable option, whereby the integration of nanoparticles (NPs) can potentially augment the antibacterial effectiveness of resin cement. The objective of this study was to conduct a comprehensive literature review to assess resin cement’s antibacterial effectiveness by incorporating nanoparticles. An extensive search of PubMed and Scopus databases up to September 12, 2023, was conducted to identify relevant scholarly articles that examined and evaluated resin cement’s antibacterial effectiveness with and without the incorporation of nanoparticles (NPs). This systematic review adhered to the PRISMA guidelines for reporting the results. The search retrieved seven eligible studies. Studies indicated that resin cement with NPs significantly reduced the colony forming unit (CFU) counts compared to resin cement without NPs. Furthermore, resin cement, in addition to NPs, significantly reduced the bacterial metabolic activity compared to the control group. The use of nanoparticles (NPs) in resin cement has been shown to enhance its antibacterial properties, possibly mitigating the occurrence of secondary caries. Future clinical trials are required to validate the beneficial effects of NPs in conjunction with resin cement in the prevention of secondary caries.